Developing the family of picolinate ligands for Mn2+ complexation - Pujales Paradela, Rosa; et al. (Dalton Transactions, 2017)
We have reported here a series of ligands containing pentadentate 6,6'-(azanediylbis(methylene)) dipicolinic acid units that differ in the substituent present at the amine nitrogen atom (acetate: H(3)DPAAA; phenyl: H(2)DPAPhA; dodecyl: H(2)DPAC12A; 4-hexylphenyl: H(2)DPAC6PhA). The protonation constants of the hexadentate DPAAA(3-) and pentadentate DPAPhA(2-) ligands and the stability constants of their Mn2+ complexes were determined using pH-potentiometry (25 degrees C, 0.15 M NaCl). The mono-hydrated [Mn(DPAAA)](-) complex (log K-MnL = 13.19(5)) was found to be considerably more stable than the bis-hydrated [Mn(DPAPhA)] analogue (log K-MnL = 9.55(1)). A detailed H-1 and O-17 NMR relaxometric study was carried out to determine the parameters that govern the proton relaxivities of these complexes. The [Mn(DPAC12A)] complex, which contains a dodecyl lipophilic chain, forms micelles in solution characterized by a critical micellar concentration (cmc) of 96(9) mu M. The lipophilic [Mn(DPAC6PhA)] and [Mn(DPAC12A)] derivatives form rather strong adducts with Human Serum Albumin (HSA) with association constants of 7.1 +/- 0.1 x 10(3) and 1.3 +/- 0.4 x 10(5) M (1), respectively. The X-ray structure of the complex K(H2O)(4)[Mn(DPAAA)(H2O)](2) shows that the Mn2+ ion in [Mn(DPAAA)](-) is coordinated to the six donor atoms of the ligand, a coordinated water molecule completing the pentagonal bipyramidal coordination environment.